Vulnerability of Motivation Schemes in Enhancing Site Workers Productivity for Construction Industry's Sustainability in Nigeria - Adedokun, Olufisayo Adewumi; Ibironke, Olajide Timothy; Olanipekun, Ayokunle Olubunmi (International Journal of Sustainable Construction Engineering and Technology, 2013)
The construction industry provides appreciable employment for the unskilled and semi-skilled labour considering the nature of most activities carried out on construction sites. However, the productivity of this categories of labour have trended poor overtime. This study therefore assessed the financial and non financial motivational schemes; in light of their preference to construction site workers so as to assure on their vulnerability in enhancing productivity. The data collected through the administration of questionnaires to construction site operatives were analysed using the relative importance index (RII). The research instrument was also legitimized with content validity index (CVI) for items ? 0.80 and cronbach alpha value, as a measure of internal consistency, ? 0.70. Allowances, wages stock option and bonuses are the financial motivators while delegation, independence and autonomy, facilities for transportation are the non financial motivations that are important to site workers on construction sites. Giving praises, encouragement to make contributions, free medical care, availability of relaxation centres and first aid provision are the motivation schemes that site operatives believed to enhance their productivity. This paper concludes that both financial and non financial motivational schemes are important to enhancing the productivity of operatives on construction sites. The vulnerable motivational schemes to the enhancement of productivity, as revealed in this study is recommended to the construction and subcontracting firms, foremen, clerk of works, site supervisors, site engineers and all other stakeholders in ensuring a maximum output for a unit input from site operatives.